2005
DOI: 10.1007/s11144-005-0284-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the lattice oxygen mobility on the activity of Gd-doped ceria promoted with pt in syngas generation from methane at short contact times

Abstract: The activity of Pt/Ce 1-x Gd x O 2-y samples in steam and dry reforming of methane at short contact times correlates with the lattice oxygen mobility. For the partial oxidation of methane (POM), the oxygen mobility should be optimized to prevent methane combustion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Chemical Behavior with Respect to Catalytic Conversion of Methane. Recently it was shown that nanostructured cerium dioxide doped with different rare earth elements and promoted with noble metals may serve as an efficient catalyst for synthesis gas generation via selective oxidation as well as steam or dry reforming of methane. , The syngas yield was found to depend on the lattice oxygen mobility, which in turn can be tuned in the nanostructured ceria system by the appropriate choice of the kind and amount of dopant ions. To further investigate the catalytically relevant redox properties of the Gd-doped ceria, additional temperature-programmed- reduction experiments have been performed using 1% CH 4 in He as a reducing agent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chemical Behavior with Respect to Catalytic Conversion of Methane. Recently it was shown that nanostructured cerium dioxide doped with different rare earth elements and promoted with noble metals may serve as an efficient catalyst for synthesis gas generation via selective oxidation as well as steam or dry reforming of methane. , The syngas yield was found to depend on the lattice oxygen mobility, which in turn can be tuned in the nanostructured ceria system by the appropriate choice of the kind and amount of dopant ions. To further investigate the catalytically relevant redox properties of the Gd-doped ceria, additional temperature-programmed- reduction experiments have been performed using 1% CH 4 in He as a reducing agent.…”
Section: Resultsmentioning
confidence: 99%
“…This opens new possibilities to further modify and improve the materials with respect to possible catalytic applications. Recently, we reported on nanostructured ceria doped with Sm, Bi, Pr, , and Gd , prepared by the so-called “Pechini method” . The materials exhibit high oxygen ion conductivity with the lattice oxygen mobility depending on the kind and amount of dopant ions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mobility of oxygen ions in the ceria lattice may play an important role in the catalytic performance influencing oxygen supply from the bulk to active surface centers and the kinetics of redox process. For instance, an inverse correlation between lattice oxygen mobility and selectivity towards POM was observed for Ce 1Àx Gd x O 2Àd fluorite-type solid solutions [23]. Higher oxygen mobility in Ce 0:9 Sm 0:1 O 2Àd compared to that in Ce 0:45 Zr 0:45 La 0:10 O 2Àd [19] should promote the activation of oxygen ions at the platinum/ oxide interface and result in faster oxidation of methane and/or partial oxidation products.…”
Section: Xrdmentioning
confidence: 99%